Gender and social mobility: Exploring gender attitudes and women's labour force participation - Nancy Luke (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Women have historically been overlooked in research on social mobility. In contrast, new research focuses on the intergenerational transmission of gender attitudes and norms as determinants of women's labour force participation in industrialized countries. This paper discusses the measurement of gender attitudes and reviews research findings. Studies reveal that gender attitudes are a key transmission mechanism for intergenerational economic mobility beyond wealth and other economic factors. Mothers' egalitarian views and less-restrictive gender norms promote greater labour force participation for daughters and daughters-in-law. There are few investigations in developing countries, where restrictive gender attitudes and norms are more pervasive and could potentially have greater impact in shaping women's labour force participation. The paper concludes with a brief case study of women's labour force participation in India, where the direct link between gender attitudes and women's labour market engagement could provide a further explanation for its recent decline.
Keywords: J2; J16; Z1; Z13; 330; gender; gender attitudes; norms; women's labour force participation